1987
DOI: 10.1136/thx.42.11.870
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of human bronchiolar smooth muscle responsiveness in vitro with histological signs of inflammation.

Abstract: A study was carried out to test the hypothesis that chronic inflammation is associated with increased sensitivity or contractility of human airway smooth muscle. Bronchiolar strips from 30 patients, 12 of whom had chronic bronchitis, were examined in the organ bath for their responses to histamine, methacholine, and leukotriene (LT) C4. The same airways were also studied histologically and small airway disease was quantified by subjective grading of the degree of inflammatory cell infiltration, smooth muscle h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
1

Year Published

1989
1989
2008
2008

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 17 publications
0
6
0
1
Order By: Relevance
“…Obstructive airways diseases, such as asthma and COPD, are characterized by airway hyperresponsive- Hypercellular lung tissue (endothelial cells and type I pneumocytes) [6,23,32] Pulmonary hypertension [128] Augmented endothelium mediated vascular relaxation [6] Increased Ca 2+ sensitization of vascular smooth muscle [29] Reduced exercise tolerance [32] Reduced transendothelial macromolecule transport [120] Reduced pulmonary inflammation in response to LPS exposure [130] ness to inhaled and endogenous bronchoconstrictors [36], which is in part accompanied by contractile abnormalities of the airway smooth muscle [37][38][39][40]. Notably, caveolin-1 and caveolin-2 are abundant in airway smooth muscle (Fig.…”
Section: Caveolae and Caveolins In The Regulation Of Airway Tone Airwmentioning
confidence: 99%
“…Obstructive airways diseases, such as asthma and COPD, are characterized by airway hyperresponsive- Hypercellular lung tissue (endothelial cells and type I pneumocytes) [6,23,32] Pulmonary hypertension [128] Augmented endothelium mediated vascular relaxation [6] Increased Ca 2+ sensitization of vascular smooth muscle [29] Reduced exercise tolerance [32] Reduced transendothelial macromolecule transport [120] Reduced pulmonary inflammation in response to LPS exposure [130] ness to inhaled and endogenous bronchoconstrictors [36], which is in part accompanied by contractile abnormalities of the airway smooth muscle [37][38][39][40]. Notably, caveolin-1 and caveolin-2 are abundant in airway smooth muscle (Fig.…”
Section: Caveolae and Caveolins In The Regulation Of Airway Tone Airwmentioning
confidence: 99%
“…There are few studies comparing the force-generating capacity of asthmatic airway smooth muscle with normal muscle (22)(23)(24)(25)(26)(27). At least one (25) showed increased constrictor sensitivity, but others showed normal or reduced contractile function.…”
Section: Functional Effects Of Airway Smooth Muscle Proliferation Andmentioning
confidence: 99%
“…Asthmatics have a mixed hypersensitivity and hyper-reactivity to the acute bronchoconstrictor effects of inhaled histamine with a shift to the left and an increase in the slope of the log doseresponse curve (Snashall, 1987) and, in two recent studies, lung tissues from asthmatics was found to be hyper-reactive to spasmogens (De Jongste et al, 1987;Bai, 1990).…”
Section: Eosinophilia and Lung Hyper-responsivenessmentioning
confidence: 99%